2020
DOI: 10.1038/s41433-019-0761-z
|View full text |Cite
|
Sign up to set email alerts
|

The Royal College of Ophthalmologists’ National Ophthalmology Database study of cataract surgery: Report 7, immediate sequential bilateral cataract surgery in the UK: Current practice and patient selection

Abstract: Background Cataract extraction is the most frequently performed surgical intervention in the world and demand is rising due to an ageing demography. One option to address this challenge is to offer selected patients immediate sequential bilateral cataract surgery (ISBCS). This study aims to investigate patient and operative characteristics for ISBCS and delayed bilateral cataract surgery (DSCS) in the UK. Methods Data were analysed from the Royal College of Ophthalmolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 16 publications
1
37
0
6
Order By: Relevance
“…Posterior capsular rupture (PCR) is a complication of cataract surgery that can be associated with significantly worse visual outcomes [44]. The Royal College of Ophthalmologists of England National Ophthalmology Database study of cataract surgery for cases between 2010 and 2018 reported a mean PCR rate of just less than 1% [45]. The hypothesis that previous intravitreal therapy is a predictor of increased risk of PCR during cataract surgery was tested on a large registry of eyes undergoing cataract surgery from 20 UK Hospital Trusts between 2004 and 2014 [46].…”
Section: Managing Posterior Capsular Rupture or Zonular Dialysis During Cataract Surgerymentioning
confidence: 99%
“…Posterior capsular rupture (PCR) is a complication of cataract surgery that can be associated with significantly worse visual outcomes [44]. The Royal College of Ophthalmologists of England National Ophthalmology Database study of cataract surgery for cases between 2010 and 2018 reported a mean PCR rate of just less than 1% [45]. The hypothesis that previous intravitreal therapy is a predictor of increased risk of PCR during cataract surgery was tested on a large registry of eyes undergoing cataract surgery from 20 UK Hospital Trusts between 2004 and 2014 [46].…”
Section: Managing Posterior Capsular Rupture or Zonular Dialysis During Cataract Surgerymentioning
confidence: 99%
“…48 Currently, ISBCS in the UK is offered to limited patients who require general anaesthesia for social reasons, for example, patients with learning difficulty. 49 Post-COVID, the real benefit of bilateral surgery should be applied to carefully selected, counselled and consented patients. 50 Cataract surgery by appointment This is a model where patients self-prepare for surgery, arrive and discharge directly from the operating theatre.…”
Section: Immediate Sequential Bilateral Cataract Surgerymentioning
confidence: 99%
“… 5 In 73 centres where at least one patient had undergone ISBCS, the overall rate was 0.4% of the cataract operations performed. 6 Some commentators believe that for a routine elective procedure, ISBCS should not be undertaken as the potential benefits do not outweigh the potential harms of the protocol. 7 …”
Section: Introductionmentioning
confidence: 99%